Improving forage productivity for increased livestock production using biochar and green manure amendments - Paul, Birthe K.; Nambima Dene, Amos B.; Houehanou, Thierry D.; Cao Diogo, Rodrigue V. (20th Australian Agronomy Conference, 2022)
The rapid population growth in West African cities resulted in rising demand for animal source foods. However, this high demand for animal source food is rarely met by domestic production in Benin due to several factors, including low feed availability and poor animal nutrition, especially during the dry months, and degraded soils. To overcome this situation, the effects of maize (Zea mays) cob biochar and green manure from Gliricidia sepium and Mucuna pruriens (2 t/ha each) and their combination (1 t/ha each) were tested on Brachiaria brizantha cv. Xaraés agronomic performance over three months. The combination of biochar and green manure performed best with plant height increased by 57% (103.8 ± 17.12 cm) when compared to the un-amended control plots and each treatment alone two-month after planting. In addition, the number of leaves (22.9 ± 5.82) and the biomass determined (20.3 ± 5.64 t dry matter/ha) were highest with the combined treatment than the un-amended control plots three-months after planting. B. brizantha cv. Xaraés, fertilized with locally available biochar and green manure, could contribute significantly to increasing feed availability at farm level and boost meat and milk production.